[Haskell-beginners] Beginners Digest, Vol 56, Issue 33
xiao Ling
lingxiao at seas.upenn.edu
Sat Feb 23 01:27:28 CET 2013
Hi All: How do you define a function of signature h :: M Int -> M Int -> M
Int so that h ( M x ) ( M y ) = M ( x + y ), but without unwrapping the
value from the monad?
This question is from the article "Trivial Monad" found at
http://blog.sigfpe.com/2007/04/trivial-monad.html. The provided answer is
h x y = x >>= (\x -> g x y)
or equivalently ( in context of the article )
h :: M Int -> M Int -> M Int
h x y = bind ( \x-> g x y ) x
where g is
g :: Int -> W Int -> W Int
g x y = y >>= (return . (+x))
for the monad:
data M a = M a deriving Show
Now I am a little confused, how can you put x in g if it takes an Int as
first parameter but x is M Int?
Thanks!
-------------- next part --------------
An HTML attachment was scrubbed...
URL: <http://www.haskell.org/pipermail/beginners/attachments/20130222/1e237638/attachment-0001.htm>
More information about the Beginners
mailing list